Major Socio-Economic Factors Influencing Environmental Concern. Study on Several European Union Countries - Ulman, Simona-Roxana; Dobay, Krisztina Melinda; Mihai, Costica; Cautisanu, Cristina; Anisoara Gavrilescu, Camelia (Transformations In Business & Economics, 2026)
Our study aims to measure the environmental concern across some EU member states and to provide a better understanding of its determinants. Using data from the World Values Survey, there were firstly analysed the individual perceptions (care for environment, perspective on environmental pollution, protecting environment vs. economic growth), then active participation (membership in an environmental organization, financing ecological organization, participation in pro-environmental demonstration) and, lastly, integrating both in one general composite index. Our results showed that Poland, Romania, and Spain register the lowest levels of general environmental concern, while Sweden attains the highest level among the analysed EU countries. Although both Spain and Sweden are advanced economies, there are significant differences between their national general environmental concerns. Using the Binomial Logistic Regression, we found that the position of an individual highly concerned with environmental problems is mainly influenced by (1) age, nature of tasks, post-materialist values, and satisfaction in life in Sweden, while, (2) in Spain, the most important determinants are educational level and post-materialist values. Accordingly, our findings might support better-targeted EU and national environmental policies.